Natural variation of Arabidopsis thaliana responses to Cauliflower mosaic virus infection upon water deficit - Bergès, Sandy E. (PLoS Pathog, 2020)
Plant virus pathogenicity is expected to vary with changes in the abiotic environment that affect plant physiology. Conversely, viruses can alter the host plant response to additional stimuli from antagonism to mutualism depending on the virus, the host plant and the environment. Ecological theory, specifically the CSR framework of plant strategies developed by Grime and collaborators, states that plants cannot simultaneously optimize resistance to both water deficit and pathogens. Here, we investigated the vegetative and reproductive performance of 44 natural accessions of A. thaliana originating from the Iberian Peninsula upon simultaneous exposure to soil water deficit and viral infection by the Cauliflower mosaic virus (CaMV). Following the predictions of Grime’s CSR theory, we tested the hypothesis that the ruderal character of a plant genotype is positively related to its tolerance to virus infection regardless of soil water availability. Our results showed that CaMV infection decreased plant vegetative performance and annihilated reproductive success of all accessions. In general, water deficit decreased plant performance, but, despite differences in behavior, ranking of accessions tolerance to CaMV was conserved under water deficit. Ruderality, quantified from leaf traits following a previously published procedure, varied significantly among accessions, and was positively correlated with tolerance to viral infection under both well-watered and water deficit conditions, although the latter to a lesser extent. Also, in accordance with the ruderal character of the accession and previous findings, our results suggest that accession tolerance to CaMV infection is positively correlated with early flowering. Finally, plant survival to CaMV infection increased under water deficit. The complex interactions between plant, virus and abiotic environment are discussed in terms of the variation in plant ecological strategies at the intraspecific level.